Training system for coal mine full-hydraulic drilling rig based on virtual reality technology - WANG Tianlong; QIAO Jie; PENG Tao; YAO Yafeng; LIU Ruiquan (Gong-kuang zidonghua, 2018)
In view of problem of unsatisfactory effect of traditional training for coal mine full-hydraulic drilling rig, a training system for coal mine full-hydraulic drilling rig based on virtual reality technology was developed. The system is consisted of lower computer and upper computer, and communication between the lower computer and the upper computer is realized through FX2N series PLC programming interface. The lower computer uses PLC to collect and process control instruction of drilling rig virtual console. The upper computer applies Quest3D virtual software to realize virtual drilling rig and scene setting, key parts virtual disassembly and virtual drilling rig operation programming. The system shortens training period and reduces training cost with good human-computer interaction performance and simple operation.